The corridor : a pilot project on an incremental social housing, Navaron, Jhikargacha, Jessore. - Ahmed, Tousib (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2017.